2010
DOI: 10.1007/s10517-010-0958-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Selenium-Containing Products on Antioxidant Enzyme Activity in the Kidneys, Liver, and Blood of Guinea Pigs

Abstract: The antioxidant system of some tissues in guinea pigs with no selenium deficiency was studied after treatment with selenium-containing products. Activity of a selenium-containing enzyme glutathione peroxidase was significantly reduced in the kidneys and blood. The kidneys were characterized by low activity of glutathione reductase and high activity of SOD. These features illustrate the development of oxidative stress in the kidneys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…Therefore, there is a clear relationship between Se deficiency, GPx activity, and protein oxidation in liver, which is also parallel to low liver development. This increase in SOD activity in conditions of Se deficiency has also been detected by other authors in mouse liver (Stỳblo et al 2007), as well as in other tissues (Sirota 2010, Erkekoglu et al 2012. This increase in SOD activity could be to compensate the formation of more superoxide generated by mitochondrial dysfunction, caused in part by the increase in reactive oxygen species (ROS; Shi et al 2012), by the decrease in Se levels that are related to a correct mitochondrial function and its biogenesis (Mehta The results are expressed as meanGS.E.M.…”
Section: Antioxidative Defense and Oxidative Stress Markers In Liversupporting
confidence: 86%
“…Therefore, there is a clear relationship between Se deficiency, GPx activity, and protein oxidation in liver, which is also parallel to low liver development. This increase in SOD activity in conditions of Se deficiency has also been detected by other authors in mouse liver (Stỳblo et al 2007), as well as in other tissues (Sirota 2010, Erkekoglu et al 2012. This increase in SOD activity could be to compensate the formation of more superoxide generated by mitochondrial dysfunction, caused in part by the increase in reactive oxygen species (ROS; Shi et al 2012), by the decrease in Se levels that are related to a correct mitochondrial function and its biogenesis (Mehta The results are expressed as meanGS.E.M.…”
Section: Antioxidative Defense and Oxidative Stress Markers In Liversupporting
confidence: 86%
“…Alpha-toc protects the unsaturated fatty acids of membrane phospholipids from oxidative degeneration through the formation of unreactive radical species and breaking the free radical reactions chain [36]. It is a useful free radical scavenger against stress conditions in several tissues [46]. The increases in selenium-dependent antioxidant enzymes activities decrease free radical-mediated lipid peroxidation and regenerate reduced glutathione.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that alpha-toc has the ability to protect against lipid peroxidation through the oxygen scavenging activity, neutralizing the lipid peroxidation and unsaturated membrane lipids [47]. Stimulation of the radical scavenger and the increase in the antioxidant defense mechanism might be the protecting role of selenium against lipid peroxidation [46].…”
Section: Discussionmentioning
confidence: 99%